The Relationship Between Social Commerce Design Models on Shopee Users' Purchase Decisions - Jonathan Weiyn Rumende; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2021)
The rapid advancement of information technology in today's digital era has made the shopping axis undergo many changes in its development. Shopping online through social commerce is a new trend as the development of technology and the current market. Social commerce is a new online shopping platform, which allows shoppers to make transactions and purchases directly from an e-commerce portal through their handsets along with social interactions such as on social media. The purpose of this study is to find out the differences between the determinants of social commerce designs in relation to purchasing decisions by users of these social commerce tools. This study uses an empirical test that begins with a literature study and a questionnaire. Questionnaires were distributed to social commerce users, in this case Shopee. The data that has been collected in quantitative form is then processed with the help of the SPSS application. The data will begin to be processed by testing the validity and reliability, and regression. The results of this study produce factors that need to be considered and considered to develop a social commerce-based business that is needed by Indonesian businesses and businesses.